PENDAMPINGAN PSK (PEKERJA SEKS KOMERSIL) BERBASIS PENDEKATAN SPIRITUAL KEAGAMAAN DI KABUPATEN PROBOLINGGO - Siti Maryam; Muhammad Hifdil Islam; Sisi Nora Viara (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
Prostitutes (PSK) are a notable phenomenon that continues to thrive and grow in various parts of the world. Probolinggo Regency is no exception, as it cannot be deemed free from prostitution practices. Several locations serve as centers for these activities, which are challenging to control despite numerous enforcement efforts by the authorities. The goal of this community service (PkM) activity is to touch the spiritual lives of the Pasir Panjang residents. By employing ABCD approach, the researchers aim to explore the potential possessed by the Pasir Panjang community. A religious-spiritual approach was chosen as a way to encourage the community to reconnect with their Creator. Based on a mutual agreement, this service activity was implemented through two programs: Individual spiritual guidance and Completion of individual activity reports. After two months of implementing these programs, no significant results have been observed. Therefore, further assistance is needed.